Caffeine improved cycling trial performance in mentally fatigued cyclists, regardless of alterations in prefrontal cortex activation - Franco-Alvarenga, P. E.; Brietzke, C.; Canestri, R.; Fagundes Goethel, M.; Hettinga, F.; Meireles Santos, T.; Oliveira Pires, F. (Physiology & Behavior, 2019)
Purpose: To verify whether caffeine (CAF) could increase the prefrontal cortex (PFC) activation and improve 20 km cycling time trial (TT20km) performance in mentally fatigued cyclists. Methods: After preliminary TT20km, twelve recreational cyclists (VO2MAX of 58.9 ± 6.2 mL kg min-1) performed a familiarization with a cognitive test to induce mental fatigue (MF) and psychological scales. Thereafter, they performed: 2) a baseline TT20km; 3) a mentally fatigued TT20km (MF); 4 and 5) a mentally fatigued TT20km after CAF (MF + CAF) or placebo (MF + PLA) ingestion, in a double-blind, counterbalanced design. Performance and psychological responses were obtained throughout the TT20km, while PFC electroencephalography (EEG) theta wave was obtained before and after the mental fatigue test. Results: The mental fatigue-induced increase in EEG theta wave ( ~ 4.8%) was reverted with CAF ( 8.8%) and PLA ingestion ( 4.8%). CAF improved TT20km performance in mentally fatigued cyclists by reducing time (p = .00; ~ 1.7%) and increasing WMEAN (p = .00; ~ 3.6%), when compared to MF + PLA. The RPE-power output ratio was lower (p = .01), but affect (p = .018), motivation (p = .033) and emotional arousal (p = .001) were greater throughout the TT20km in MF + CAF than in MF + PLA. Conclusions: CAF ingestion improved TT20km performance and psychological responses in mentally fatigued cyclists, despite the unaltered PFC activation.